Human Resource Management Competencies in Banking Organizations in Indonesia - Lira Agusinta; Peppy Fachrial (Syntax Corporation, 2022)
Background and purpose: In its development, fintech has entered the 4.0 era where it has developed by facilitating the financial system and it is feared that it could become a threat to the world of conventional banking. Therefore, this study aims to develop competency strategies needed by banks in facing the disruption of the fintech 4.0 era. Design/Methodology/Approach: In this study the research approach used is a quantitative approach (post positivist). Data collection is carried out using research instruments, statistical or quantitative analysis, with the aim of testing predetermined hypotheses. Results: The results show that competency-based practice contributes positively to the bottom line, and that contributions to organizations are related to the roles of individuals not to their jobs. Additionally, efforts designed for employee commitment have the potential to generate positive returns, and that training and development are seen as drivers of future success. Conclusion: Even though banking has similar products with fintech companies, it has a different character where banks have a higher prudential principle. Competency is needed for bank employees in dealing with fintech 4.0, namely E-KYC, Payment Gateway, Big Data, Cloud Infrastructure, Artificial Intelligence and digital signatures besides that it also requires the ability to innovate, a willingness to learn and change, and be able to provide creative encouragement where they work